2020
DOI: 10.1111/nbu.12461
|View full text |Cite
|
Sign up to set email alerts
|

Do modern types of wheat have lower quality for human health?

Abstract: Wheat is the major staple food in Western Europe and an important source of energy, protein, dietary fibre, minerals, B vitamins and phytochemicals. Plant breeders have been immensely successful in increasing yields to feed the growing global population. However, concerns have been expressed that the focus on increasing yield and processing quality has resulted in reduced contents of components that contribute to human health and increases in adverse reactions. We review the evidence for this, based largely on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 56 publications
2
22
1
Order By: Relevance
“…S1), showing that wheat breeders did not select for changes in ATI contents in Central and Eastern Europe in the last century, neither directly nor indirectly via correlation with other traits. This confirms our experience from many discussions with breeder colleagues and is also in accord with a study that found no significant difference between old and modern Austrian wheat evaluated for total ATI content (Shewry et al 2020). This is in contrast to statements that modern bread wheat cultivars have increased ATI content compared to old varieties as originally hypothesized by Junker et al (2012), and now widely stated in popular press and social media.…”
Section: Breeding Wheat Cultivars For Lower Ati Contentsupporting
confidence: 90%
“…S1), showing that wheat breeders did not select for changes in ATI contents in Central and Eastern Europe in the last century, neither directly nor indirectly via correlation with other traits. This confirms our experience from many discussions with breeder colleagues and is also in accord with a study that found no significant difference between old and modern Austrian wheat evaluated for total ATI content (Shewry et al 2020). This is in contrast to statements that modern bread wheat cultivars have increased ATI content compared to old varieties as originally hypothesized by Junker et al (2012), and now widely stated in popular press and social media.…”
Section: Breeding Wheat Cultivars For Lower Ati Contentsupporting
confidence: 90%
“…Overall, these products provide a significant portion of calories and proteins to human diets; also, they are an important source of bioactive compounds that may contribute to a healthy diet [2]. Among others, the most common bioactive compounds of wheat include dietary fiber, vitamins, micronutrients, and phytochemicals, which are mainly located in the outer layers of the kernel, typically in the bran, aleurone, and germ tissues [3]. A high number of in vitro, in vivo, and epidemiological studies have shown the significant health-related benefits associated with the consumption of bran-rich or whole-wheat foods [4], together with a decreased risk of non-communicable diseases, such as type 2 diabetes mellitus, cardiovascular disorders, and colorectal cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…An extensive compositional analysis (Shewry et al, 2020) of 150 varieties of wheat obtained from seed banks (including older varieties from the 19th and early 20th centuries and modern types produced by intensive breeding) that were grown, harvested and milled under identical conditions, showed that the protein content of wheat has declined slightly from older to modern types (Figure 2). This decrease is associated with a parallel increase in the content of starch, which is responsible for the higher yields.…”
Section: Do Ancient Wheats Contain Less Gluten Than Bread Wheat?mentioning
confidence: 99%
“…An extensive compositional analysis (Shewry et al, 2020) of 150 varieties of wheat obtained from seed F I G U R E 1 Condensed history of wheat. Natural crossing of early diploid wheat ancestors (with the AA and BB genomes) led to the development of tetraploid emmer wheat (AABB genomes), which subsequently became domesticated and diversified into durum wheat.…”
Section: Do Ancient Whe Ats Contain Less Gluten Than Bre Ad Whe At?mentioning
confidence: 99%